Serotypes and clonal types of penicillin-susceptible streptococcus pneumoniae causing invasive disease in children in five Latin American countries - Zemlicková, Helena (2005)
Fil: Zemlicková, Helena. The Rockefeller University, New York; Estados Unidos.